The anthropology of traps: Concrete technologies and theoretical interfaces - Corsín Jiménez, Alberto (Journal of material culture, 2019)
Traps connect not only predator and prey, but mind and materiality, technology and landscape, and infrastructure and ecology. Through them, bodies, knowledge practices, materials and environments are assembled in transformative encounters which, because of their lethal agency, have emotive and moral force. In this Introduction to the Special Issue, the authors explore the conceptual bridges and disciplinary admixtures invited by ethnographic attention to traps. They review a history of attention to traps, which is in the main a history of neglect and epistemological bias. As humble hunting technologies, traps have been secondary in status to the heroic chase, and the lifeways of trappers at the frontiers of empires have been neglected. Meanwhile traps have featured as archetypes and prototypes in evolutionist discourses focusing on technology, and human crafty intelligence in its invention and advancement. The authors trace these threads from the 19th century to contemporary anthropology and archaeology, and propose conceptual and practical lines for future analysis and research collaboration.